2021
DOI: 10.1159/000515854
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Healthcare Costs in the Aging Hepatitis B Population of Japan: A Nationwide Real-World Analysis

Abstract: Introduction: Advancing age, comorbidity, and financial burden have been observed in chronic hepatitis B (CHB) patients globally. As Japan is leading the world in aging demographics, similar real-world data are urgently needed for its CHB population to inform all stakeholders. Methods: This cross-sectional study characterized the demographics, comorbidities, and healthcare costs of a large Japanese real-world adult (≥18 years) CHB patient (ICD-10: B18.1) population from the Medical Data Vision database from 01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
5
10
0
Order By: Relevance
“…Recent data have suggested that patients with CHB have aged globally in the past decade [ 36 , 37 , 38 , 39 , 40 ], and as such, the prevalence of CHB patients with comorbidities including MetS has increased substantially, furthering highlighting the need for further research in this area. Additionally, data regarding the underlying biologic mechanisms between chronic HBV infection and MetS remains sparse.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Recent data have suggested that patients with CHB have aged globally in the past decade [ 36 , 37 , 38 , 39 , 40 ], and as such, the prevalence of CHB patients with comorbidities including MetS has increased substantially, furthering highlighting the need for further research in this area. Additionally, data regarding the underlying biologic mechanisms between chronic HBV infection and MetS remains sparse.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Another significant finding from this study was the divergence from the perspectives of patients and family caregivers on information needs and decision-making. Unmet informational demands are often recognised in patients with advanced cancer and family caregivers in general and occur earlier in the HCC disease course 50. Additional problems arise as a result of the numerous communication issues, such as difficulty in verbalising and ambiguity regarding the best method to inform the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, following the fourth decade of life, physiologic renal function decline is expected at about 8 mL/min/1.73m per decade, 64 which is very relevant as the CHB population continues to age, with 42% already 55 years or older in 2015 in the United States as as high as 60% being 65 years or older in 2016 elsewhere such as Japan. [65][66][67][68][69] Notably, observational data from population-based studies from both the United States and Asia have also found CHB to associate with higher prevalence and incidence of chronic kidney disease. 65,[70][71][72] For patients at risk of nephrotoxicity or for those taking TDF, 73 creatinine clearance (eGFR) and serum phosphorus should be monitored every 3 months during the first year of therapy.…”
Section: Monitoring For Renal Toxicitymentioning
confidence: 99%